Languages of Written and Oral Communication between Russian Emperors and Electors of the Holy Roman Empire, 1725–1799 - M. A. Petrova (Vestnik MGIMO-Universiteta)
This article, based on unpublished materials from the Archive of Foreign Policy of the Russian Empire, represents the first historiographical analysis of the languages used in official correspondence—such as letters of credence, recall, and notifications—between the secular and ecclesiastical electors of the Holy Roman Empire and Russian emperors during the eighteenth century. Employing the methodological framework of diplomatics, an auxiliary historical discipline, the author utilizes formulaic analysis to examine the mandatory expressions and formulas in the opening and closing protocols of these letters. These linguistic conventions provide insights into the social status of both sender and recipient, reflecting the hierarchical nature of diplomatic relationships.The article contributes to the growing interest in early modern diplomatic languages, a field that has gained traction in recent foreign historiography, particularly in studies of negotiation practices at international congresses. Archival research reveals distinct patterns in the linguistic practices of the electors. Saxon electors corresponded with Russian emperors in German, while the electors of the Palatinate and Bavaria initially used Latin before transitioning to German in the mid-eighteenth century. Ecclesiastical electors—the archbishops of Mainz, Trier, and Cologne—also wrote in German. On rare occasions, French was used. Conversely, Russian monarchs adhered to tradition, drafting official correspondence in Russian with German translations attached.The article concludes that the choice of language serves as a formal indicator of the nature of relationships between rulers, highlighting the distinction between sovereign monarchs and electors, who, de jure, remained vassals. This hierarchical disparity is further reflected in the use of kinship terms within the correspondence. For example, Russian emperors addressed secular electors not as "brothers" or "sisters"—terms typically reserved for sovereign equals— but as "uncles," "aunts," or, later, "in-laws" (occasionally "cousins"). These designations underscored the unequal status of the correspondents.Additionally, the correspondence sheds light on the process by which the influential Estates of the Holy Roman Empire recognized the imperial title of the Russian monarchs. By analyzing the linguistic and formal characteristics of these letters, the study provides new insights into the social and political dynamics of eighteenth-century diplomacy.